An efficient optimization of an irreversible Ericsson refrigeration cycle based on thermo-ecological criteria. (1st August 2022) - Prajapati, Parth; Patel, Vivek; Jouhara, Hussam
Highlights: Thermo-ecological problem of Ericsson refrigeration cycle is developed and solved. Multi-objective optimization of Ericsson refrigerating cycle is investigated. Investigation of the effect of operating parameters on the system performance. Investigation of the sensitivity of design variables on the thermo-ecological objective. Abstract: In the present work, a multi-objective optimization study of an irreversible Ericsson cycle is carried out to evaluate a cryogenic refrigerator system based on thermal and ecological performance. The coefficient of performance, cooling load and input power are considered as objective functions along with an ecological objective function and the effect of variables like the effectiveness of the heat sink heat exchanger, the effectiveness of the heat source heat exchanger, the temperature ratio of heat sink and heat source and the capacitance rate of the heat sink and heat source. Objective functions are optimized using a heat transfer search optimization algorithm for two different scenarios, and the Pareto front is obtained. The decision making method namely TOPSIS is adopted to identify the best solution among numerous optimal solutions for each scenario. The effect of design variables on thermo-ecological objective functions is explored and presented. A maximum cooling load of 3.27 kW at heat sink temperature of 172 K is obtained for a cryogenic refrigerator operating on an irreversible Ericsson cycle at an input power of 3.91 kW with a COP of the system as 0.84. Finally, the distribution of the design variables during the optimization is identified and presented.